The Age Effects on the Cognitive Processes of Intention-Based and Stimulus-Based Actions: An ERP Study - Niu, Ya-Nan; Zhu, Xinyi; Li, Juan (Frontiers in Psychology, 2017)
The functional decline in action among older adults is caused not only by physical weakness but also by cognitive decline. In this study, we aimed to compare the cognitive effects of age between intention-based and stimulus-based action modes electrophysiologically. Because age-related declines in cognitive function might proceed distinctly according to specific action modes and processes, four specific cognitive processes, action-effect binding, stimulus-response linkage, action-effect feedback control and effect-action retrieval, were investigated. We recorded event-related potentials (ERPs) during a modified acquisition-test paradigm in young (mean age = 21, SD = 2) and old (mean age = 69, SD = 5) groups. A temporal bisection task and a movement pre-cuing task were used during the acquisition and test phases, respectively. Using ERP indices including readiness potential (RP), P3, N2 and contingent negative variation (CNV) to identify these four specific processes for the two action modes, we revealed the effects of age on each ERP index. The results showed similar patterns of waveforms but consistently decreasing amplitudes of all four ERP indices in the old age group compared with the young age group, which indicates not only generally declining functions of action preparation in older adults but also age effects specific to the action modes and processes that might otherwise be mixed together under confounding experimental conditions. Particularly, an interference effect indexed by the differences in the amplitudes of CNV between congruent and incongruent tasks was observed in the young age group, which is consistent with previous behavioral reports. However, this effect was absent in the old age group, indicating a specific age-related deficit in the effect-action retrieval process of intention-based action, which might be caused by an age-related deficit in associative memory. In sum, this study investigated the cognitive processes of two action modes from a developmental perspective and suggests the importance of adding associative memory training to interventions for older adults with the aim of improving intention-based action.